Meniscus Tears in Climbing - a Triviality or Serious Concern? - Latour, Marianna Ewa; Latour, Emilia (Quality in Sport, 2024)
Introduction In the past few years, the popularity of climbing and the number of its new recreational enthusiasts increased. It became clear that there are more types of trauma than finger injuries that should be commonly associated with the sport. This overview focuses on meniscus tears as a prevalent underestimated complaint of climbers. Aim of the study We aim to bring attention to meniscus lesions and deal with mechanisms of knee injury in climbing while considering the current views on the structure, function, types of lesions, treatment methods, and results in light of topical literature. Materials and methods The methodology for the literature search involved using the keywords: ''meniscus tears'', ''climbing injury'', ''bouldering'', ''arthroscopy'', and ''meniscus repair''. The phrases were searched in the PubMed and Google Scholar databases. Conclusions We concluded that climbers should recognise acute and chronic meniscus lesions as a concern requiring training breaks, possibly further diagnosis, and adequate treatments. Moreover, awareness of the risk of this type of injury in climbing should be raised, and preventive action should be taken to limit the number of new cases.